2018
DOI: 10.1016/j.neuron.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Components HAPLN1, Lumican, and Collagen I Cause Hyaluronic Acid-Dependent Folding of the Developing Human Neocortex

Abstract: Neocortical expansion, thought to underlie the cognitive traits unique to humans, is accompanied by cortical folding. This folding starts around gestational week (GW) 20, but what causes it remains largely unknown. Extracellular matrix (ECM) has been previously implicated in neocortical expansion and here we investigate the potential role of ECM in the formation of neocortical folds. We focus on three specific ECM components localized in the human fetal cortical plate (CP): hyaluronan and proteoglycan link pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 79 publications
4
137
1
Order By: Relevance
“…The other approach is studying the effects of manipulating genes that regulate neural progenitor cell (NPC) pool sizes, neuron production and neuronal migration in a lissencephalic experimental animal, the mouse (Rash et al, ; Stahl et al, ; Florio et al, ; Ju et al, ; Wang et al, ; Del Toro et al, ; Liu et al, ), and a gyrencephalic experimental animal, the ferret (Masuda et al, ; Nonaka‐Kinoshita et al, ; Poluch & Juliano, ; Shinmyo et al, ; Toda et al, ). In addition, a recent report has linked changes in stiffness of human fetal neocortex tissue to neocortical folding in an ex vivo system, suggesting a role of biophysical parameters in the context of human neocortical folding (Long et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The other approach is studying the effects of manipulating genes that regulate neural progenitor cell (NPC) pool sizes, neuron production and neuronal migration in a lissencephalic experimental animal, the mouse (Rash et al, ; Stahl et al, ; Florio et al, ; Ju et al, ; Wang et al, ; Del Toro et al, ; Liu et al, ), and a gyrencephalic experimental animal, the ferret (Masuda et al, ; Nonaka‐Kinoshita et al, ; Poluch & Juliano, ; Shinmyo et al, ; Toda et al, ). In addition, a recent report has linked changes in stiffness of human fetal neocortex tissue to neocortical folding in an ex vivo system, suggesting a role of biophysical parameters in the context of human neocortical folding (Long et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Together with our 356 data demonstrating that HA synthesis is required prior to heart tube formation to promote 357 cardiac morphogenesis ( Fig S6), this suggests that the ECM environment generated early 358 during heart development is crucial for continual and/or maintenance of chamber 359 morphogenesis. Interestingly, recent studies have demonstrated that Hapln1 is the key element 360 required for tissue folding in the human neocortex, and that HA is required to maintain the 361 architecture of the tissue after folding has occurred (Long et al 2018). In light of this, we 362…”
mentioning
confidence: 99%
“…Among the mechanisms involved in gyrification are proposals involving differential expansion of superficial versus deep cortical layers, or tension exerted by the radial glia that anchor the bottom of sulci to the ventricular surface, or by close-range corticocortical axons connecting neighboring areas (Rash & Rakic, 2014;Rash et al, 2019;van Essen, 1997). More recent models propose a role of cellular and molecular processes, like changes in intercellular adhesion during neuronal migration, or in the extracellular matrix producing differential tissue stiffness, or even in changes in sodium flux that interfere with neuronal migration (Borrell, 2018;Del Toro et al, 2017;Long et al, 2018;Smith et al, 2018). More recent models propose a role of cellular and molecular processes, like changes in intercellular adhesion during neuronal migration, or in the extracellular matrix producing differential tissue stiffness, or even in changes in sodium flux that interfere with neuronal migration (Borrell, 2018;Del Toro et al, 2017;Long et al, 2018;Smith et al, 2018).…”
Section: Brain Growth In Amniotesmentioning
confidence: 99%
“…Other authors consider geometrical constraints for the optimization of connectivity in large brains (Herculano-Houzel, Mota, Wong, & Kaas, 2010;Mota & Herculano-Houzel, 2015), whereas some propose physical models of material expansion (Tallinen, Chung, Biggins, & Mahadevan, 2014). More recent models propose a role of cellular and molecular processes, like changes in intercellular adhesion during neuronal migration, or in the extracellular matrix producing differential tissue stiffness, or even in changes in sodium flux that interfere with neuronal migration (Borrell, 2018;Del Toro et al, 2017;Long et al, 2018;Smith et al, 2018). We consider that molecular and cellular processes driving gyrification may result from natural selection that favors mutations that facilitate folding, thus minimizing the mechanical pressures exerted during brain growth that limit brain development.…”
Section: Brain Growth In Amniotesmentioning
confidence: 99%